Environmental and metabolic animal physiology - Prosser, C. Ladd (ed.). (New York, New York Wiley-Liss, 1991)
"Comparative animal physiology, fourth edition." "This book, Environmental and metabolic animal physiology, and its companion volume, Neural and integrative animal physiology, together comprises the fourth edition of Comparative animal physiology"--Pref.
Keywords: Physiology, Comparative; Adaptation (Physiology); Homeostasis; Metabolism